The Need for Active Methodologies at the Reino de Inglaterra School - Cano de la Cruz, Yullio (2019)
The need for more learning environments focused on active methodologies, part of an effort by the Ministry of Education in Ecuador to improve quality standards of the country’s educational system, served as the basis for the  following study. The study endpoint was to  design a training module that would effectively teach the use of active methodologies through workshops for training Primary School Teachers from the Reino de Inglaterra Elementary School.  The methodology consisted of a quasiexperimental design with a quantitative focus for a single group that was asked to take a pretest and a posttest. The sample was intentionally non probabilistic, consisting of 14 teachers at the school who were asked to take a pretest and a posttest. The pretest did not provide significant results regarding the teacher sample group knowledge about active methodologies. This information gap was the basis of a workshops training module. We concluded the study with the posttest which revealed a high arithmetic mean validated the effectiveness of the training module to increase knowledge about active methodologies.